2013
DOI: 10.1590/s1516-35982013001000003
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of estrus in Santa Inês, Texel and Ile de France ewes in the northwest of Paraná State, Brazil

Abstract: -The incidence of estrus in nulliparous Santa Inês (n = 16), Texel (n = 16) and Ile de France (n = 15) ewes fed two levels of crude protein (CP, 12 or 16%) was monitored from July 2005 to December 2006, and seasonality in the Santa Inês breed in the south of Brazil was characterized. The solar radiation data were recorded daily, and samples of blood were collected biweekly for determination of the plasma concentration of progesterone in Santa Inês lambs at, on average, 11±1 months of age. The female Santa Inês… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
2
1
0
2
Order By: Relevance
“…However, as Texel and Suffolk ewes showed lower PR when bred in spring, this could mean a shorter reproductive season for these breeds. At a latitude similar to that in the present study, Moraes et al (2013) also found less reproductive seasonality in the Ile de France breed compared with that in Texel; other studies also reported a marked seasonality in the Suffolk breed (Dufour, 1974; Jeffcoate et al, 1984). In the present study, females crossbred between European breeds did not show seasonality, corroborating the findings by Dufour (1974), who reported a greater duration of reproductive activity throughout the year for females crossbred between Suffolk, Dorset, and Leicester compared with pure females of the same breeds.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, as Texel and Suffolk ewes showed lower PR when bred in spring, this could mean a shorter reproductive season for these breeds. At a latitude similar to that in the present study, Moraes et al (2013) also found less reproductive seasonality in the Ile de France breed compared with that in Texel; other studies also reported a marked seasonality in the Suffolk breed (Dufour, 1974; Jeffcoate et al, 1984). In the present study, females crossbred between European breeds did not show seasonality, corroborating the findings by Dufour (1974), who reported a greater duration of reproductive activity throughout the year for females crossbred between Suffolk, Dorset, and Leicester compared with pure females of the same breeds.…”
Section: Discussionsupporting
confidence: 87%
“…At a latitude similar to that in the present study, Moraes et al (2013) also found less reproductive seasonality in the Ile de France breed compared with that in Texel; other studies also reported a marked seasonality in the Suffolk breed (Dufour, 1974;Jeffcoate et al, 1984).…”
Section: Discussionsupporting
confidence: 86%
“…O levantamento revelou que 90,54% (n=335) das publicações foram oriundas de pesquisas aplicadas usando animais e 9,46% (n=35) foram revisões de literatura. De fato, sabe-se que muitas raças de ovinos apresentam sazonalidade reprodutiva (MORAES et al, 2013). Os efeitos do fotoperíodo sobre o controle hormonal reprodutivo são mediados pela melatonina pineal e a sua secreção diária é proporcional ao comprimento da noite, ou seja, na presença da luz, a secreção de melatonina é inibida (COELHO et al, 2006).…”
Section: Resultsunclassified
“…Currently, it has been suggested that the efficiency of oestrus synchronization treatments is subjected to the nutritional status of the animal before the hormone protocol (21) . In addition, several studies (24)(25)(26) have observed that protein level in the diet do not change the frequency of natural or synchronized oestrus in ewes, but it can increase the progesterone levels (25) . This information is consistent with our results, demonstrating that an increase in the protein level in diet for ewes maintained in adequate body condition did not show any significantly effect on number of animals in oestrus, but may affect the moment of estrus manifestation.…”
Section: Discussionmentioning
confidence: 99%